The Influence of Workload Aad Perceived Behavioural Control on Performance Through Motivation in Satlantas Members Kampar Police - Suarni Norawati; Rahmad Syamra (eCo-Buss, 2024)
Satlantas is one of the implementing units at the Kampar Police with the main task of providing services, educational guidance to the community regarding traffic regulations. Therefore, the performance of members of the Kampar Police Traffic Unit needs to be improved and it is necessary to know the factors that influence this performance. This research aims to determine the influence of workload and perceived behaviour control on member motivation and performance, as well as to see the influence of workload and perceived behaviour control through motivation on member performance. The sample for this research was 135 respondents with Smart PLS data analysis. The study reveal that Workload and perceived behavior control were found to have an empirically demonstrated significant impact on work motivation. Workload was also found to have a significant impact on performance, although perceived behavior control variables did not show a significant impact on performance. The study's findings also indicated that motivation had a significant impact on performance, and that workload and perceived behavior control influence performance through the work motivation of Kampar Police Traffic Unit members.